Pisapugan a documentary on the development aggression of New Clark City project and the displacement of IPs and farmers of Capas, Tarlac - Verzosa, Khalil Salih
The aim of this study is to provide an understanding of development aggression and land grabbing towards the Aetas and farmers in Capas, Tarlac. This study will also introduce and explain the aspects of development aggression and it's detrimental causes with the Aeta of Capas, Tarlac. The Bases Conversion Development Authority (BCDA) have been doing construction work for the development of New Clark City, which are in the ancestral lands of the Aetas, this is also where development aggression, privatization, globalism and neoliberalism occur. The study employed a qualitative type of research utilizing ethnographic method and counter-mapping. The data is gathered through focus group discussions, in-depth interviews, and observations noted as a participatory observant. As a course output to the research, the author produced a creative documentary with concepts of social-realism and a postmodern approach through audio/visual narrative using digital technology.